The characteristics and improvement paths of think tank construction and exchange between China and ASEAN - Zhang, Wei; Teh, Benny Cheng Guan (Penerbit Universiti Kebangsaan Malaysia, 2024)
In 2013, the Chinese government proposed to develop new types of think tanks with distinctive Chinese features. In this new era, think tanks reflect the soft power of a country. The ASEAN region is an important geographical area for China’s Belt and Road Initiative. The development of international exchanges and cooperation among think tanks under the background of new types of think tanks with distinctive Chinese features will contribute to the strengthening of international collaboration and the fostering of closer understanding. This paper adopts a qualitative analytical research method and summarizes the cooperation and exchange mode of the think tanks of China and ASEAN by examining the ranking of the think tanks of China and ASEAN and the exchange results between them. It proposes improvement paths and development strategies for the construction and exchange of Chinese and ASEAN think tanks in the context of the new types of think tanks with distinctive Chinese features. Chinese think tanks need to conduct in-depth research on the construction of a new type of think tank system that is multidisciplinary, multi-dimensional and multi-supportive while adhering to distinctive Chinese features. China's and ASEAN's think tanks should further build platforms that are more in tune with the latest developments in cooperation between the two sides, and enhance the dissemination capacity of the results of think tank construction and exchanges.